Comparison of learning performance of 2 intubating laryngeal mask airways in novice: A randomized crossover manikin study. Issue 19 (May 2017) - Liu, Zi-Jia; Yi, Jie; Chen, Wei-Yun; Zhang, Xiu-Hua; Huang, Yu-Guang
Abstract: Background: Intubating laryngeal mask airways (LMAs) such as i-gel and Aura-i could serve as rescue devices in resuscitation and further ensure the airway by facilitating trachea intubation without ventilation interruption. But data regarding intubating LMAs in novice are limited and skill degeneration without regular training has not been evaluated. So we designed this prospective randomized crossover manikin study to compare the learning performance of 2 intubating LMAs (i-gel and Aura-i). Methods: In total, 46 novice doctors participated in this study. After standardized training and finishing 3 consecutive successful intubations with both LMAs on manikin, each participant applied intubation with both LMAs in random order for initial evaluation. To evaluate skill retention, participants were reassessed 90 days later on the same manikin without retraining between times. Primary outcome was time to successful ventilation (TTV). Results: The TTV for i-gel was significantly shorter than Aura-i (initial evaluation 11.8 ± 2.9 seconds vs 22.4 ± 5.2 seconds, 90-days reevaluation 14.9 ± 3.6 seconds vs 28.9 ± 10.0 seconds, initial evaluation, P  = .001; second evaluation, P  < .001); during re-evaluation, TTV taken for i-gel and Aura-i were both significantly longer (initial evaluation, P  = .001; second evaluation, P  < .001) and ease score of insertion both increased profoundly (i-gel P  = .025; Aura-i P  < .001). In both assessments, participants preferred i-gel as easier alternative (initial evaluation, P  = .001; second evaluation, P  < .001). There was no difference in successful intubation rate, first attempt success rate, bronchoscopy assessment, and insertion score for 2 LMAs. Conclusion: Compared with Aura-i, i-gel showed a faster and easier intubation by novice doctors in this manikin study; the skill retention of intubation performance after 3 months was acceptable for both intubating LMAs, but TTV prolonged significantly.